THE DESCRIPTION OF PERSONAL PROTECTIVE EQUIPMENT MANAGEMENT AT PT X SIDOARJO - Putri Ayuni Alayyannur; Neffrety Nilamsari (Journal of Industrial Hygiene and Occupational Health, 2017)
Various sources of hazard in the workplace needs to be controlled to minimize the risk of occupational accidents and occupational diseases. PT X is one of the pharmaceutical industry in Sidoarjo, East Java. It produces more than 270 different products in different dosages and forms and is considered as one of the leading pharmaceutical manufacturers in Indonesia. Therefore, then the likelihood of accidents must be prevented. Potential hazards in PT X are very complex, including physical, chemical, biological, and mechanical hazard. Therefore, the industry makes every effort to minimize the potential hazards in accordance with the hierarchy of control. Th recommendations use of Personal Protective Equipment (PPE) as early protection measures against the hazard of accidents and occupational diseases that arise in the workplace performed after other methods first conducted. This study aimed to describe the PPE management in PT X, with observational method. Based on observations and interviews, PT X had identified the needs and requirements of PPE; selecting appropriate PPE to the type of hazards and comfort of workers; PPE training; conducting the use, maintenance and storage of PPE training; governance disposal or destruction of PPE; coaching; and inspections, but had not done an evaluation and reporting PPE. Keywords: personal protective equipment; personal protective equipment management; pharmaceutical manufacturers